2003
DOI: 10.1177/1074840702239490
|View full text |Cite
|
Sign up to set email alerts
|

Family Experiences in the Journey Through Dementia Diagnosis and Care

Abstract: Families caring for loved ones with dementia encounter multiple challenges.This study aimed to describe experiences of families seeking diagnosis and subsequent care and treatment for relatives with dementia. Using a descriptive qualitative approach, 14 family caregivers living in diverse areas of Kansas were interviewed regarding their experiences with dementia diagnosis and treatment. Initially uncertain about symptom interpretation, caregivers encountered marked delays in getting a diagnosis once they sough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(91 citation statements)
references
References 29 publications
4
85
0
2
Order By: Relevance
“…Speechly et al (2008) report that the first area of delay arose prior to contact with an HCP. Referring to the work of Teel and Carson (2003) and De Lepeleire, Heyman, and Buntinx (1998) they suggest: Some carers arranged support in the first instance rather than seeking medical advice, but in other cases, stigma and misinterpretation of symptoms contributed to the delay. Other studies have reported that carers may be uncertain about the significance of early symptoms or may gradually adapt to the changes The other area of delay was in terms of the time taken to reach a diagnosis after first contact with a health care professional.…”
Section: Please Scroll Down For Articlementioning
confidence: 95%
“…Speechly et al (2008) report that the first area of delay arose prior to contact with an HCP. Referring to the work of Teel and Carson (2003) and De Lepeleire, Heyman, and Buntinx (1998) they suggest: Some carers arranged support in the first instance rather than seeking medical advice, but in other cases, stigma and misinterpretation of symptoms contributed to the delay. Other studies have reported that carers may be uncertain about the significance of early symptoms or may gradually adapt to the changes The other area of delay was in terms of the time taken to reach a diagnosis after first contact with a health care professional.…”
Section: Please Scroll Down For Articlementioning
confidence: 95%
“…(5, 6) The dementia diagnostic workup is even more difficult for rural patients, involving consultations with multiple specialists over extended time periods. (7) Limited access to specialists means that responsibility for early diagnosis and treatment will fall on primary care physicians. (8) Rural primary care physicians identify limited access to consultants and limited community support and education resources as major barriers to dementia diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…They can't be sure, so they're just reluctant to diagnose as Alzheimer's." 40 Assessment process was probing, demoralizing and frightening for several patients. "I didn't expect him to get this; it's in my family, not his" (starts to cry).…”
mentioning
confidence: 99%